2013
DOI: 10.1002/maco.201307226
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of nickel and silver‐based brazing alloys with E85 fuel blends

Abstract: In this study, the corrosion behavior of AISI 304 fuel rail brazed joints in presence of ethanolic E85 fuel has been evaluated. The galvanic corrosion resulting from coupling steel and copper brazing alloys has been studied as it represents a potential risk for the functionality of the fuel rail and injectors. The corrosion can lead to nozzle clogging by the increase of level of solute metallic ions or rupture of the joint itself. Tests have been carried out both on specimens simulating the brazed joints and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…However, alcohol absorbs water because it is highly hygroscopic and shows ethanol impurities (i.e., organic acids, esters, and ketones), which makes metallic materials that come in contact with ethanol-gasoline highly susceptible to corrosive attacks [1][2][3]. Numerous studies have been undertaken to evaluate the corrosion behavior of metallic materials used in components of vehicle fuel systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Bahena et al [18] evaluated the corrosion behavior of four metals, including pure aluminum, chromium steel carbon steel, and copper in a 20% ethanol-80-gasoline blend using both weight loss and electrochemical impedance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…However, alcohol absorbs water because it is highly hygroscopic and shows ethanol impurities (i.e., organic acids, esters, and ketones), which makes metallic materials that come in contact with ethanol-gasoline highly susceptible to corrosive attacks [1][2][3]. Numerous studies have been undertaken to evaluate the corrosion behavior of metallic materials used in components of vehicle fuel systems [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Bahena et al [18] evaluated the corrosion behavior of four metals, including pure aluminum, chromium steel carbon steel, and copper in a 20% ethanol-80-gasoline blend using both weight loss and electrochemical impedance spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…For example, silver-based braze alloys typically have a lower corrosion rate in an industrial atmosphere than in a marine environment [2]. When used in settings where contact with certain types of fuel may occur, silver-based brazes have poor corrosion resistance that can ultimately lead to failure [3]. The effect of brazing on the corrosion behavior of the resultant parts (including parent materials) has not been widely investigated.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, during DRX, grain boundaries migrate and microvoids initially formed at grain boundaries are isolated. Therefore, the coalescence of microvoids at grain boundaries is prevented and grain boundary decohesion is retarded [31]. Previous research works [26,27] on the study of the hot ductility of TWIP steels have shown different behaviors at the intermediate temperature range compared to most plain carbon and microalloyed steels.…”
Section: Introductionmentioning
confidence: 99%